2020
DOI: 10.1038/s41598-020-66035-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Virtual Reality on evoked potentials following painful electrical stimuli and subjective pain

Abstract: Background: Virtual reality (VR) has been shown to reduce pain, however outcome parameters of previous studies have primarily been of a subjective nature and susceptible to bias. This study investigated the effect of VR on cortical processing of evoked potentials (EPs) and subjectively reported pain. Additionally, we explored whether subjects' demographic and personal characteristics modulated the effect of VR analgesia. Methods: Three VR conditions were compared in a randomized cross-over study of 30 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
2
32
2
Order By: Relevance
“…While in cardiology, the majority of devices are intended to monitor heart rhythm, others have a therapeutic purpose [8][9][10]. One such device, the virtual reality headset, is the subject of numerous studies [11][12][13][14][15] and has recently shown to improve analgesia in a small sample of patients undergoing transcatheter aortic valve implantation [16,17]. To our knowledge, this device has not been tested in other cardiac procedures.…”
Section: Introductionmentioning
confidence: 99%
“…While in cardiology, the majority of devices are intended to monitor heart rhythm, others have a therapeutic purpose [8][9][10]. One such device, the virtual reality headset, is the subject of numerous studies [11][12][13][14][15] and has recently shown to improve analgesia in a small sample of patients undergoing transcatheter aortic valve implantation [16,17]. To our knowledge, this device has not been tested in other cardiac procedures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, immersive virtual reality, rst reported by our team in the 1990s [24], is emerging as an unusually powerful adjunctive non-pharmacologic analgesic. [6,9,15,21,26,34,36,39,40,42,47,48,49,62,70] fMRI brain scans show that in addition to reducing participants subjective experience of pain, VR also reduces painrelated brain activity. [29] A follow up fMRI study showed that VR reduces pain as much as a moderate dose of hydromorphone.…”
Section: Introductionmentioning
confidence: 99%
“…[31,57] Opioid analgesics help reduce pain, and become more effective at higher doses, [2,45,50,55,74] but opioid side effects limit dose levels. [10] Furthermore, unhelpful psychological in uences can exacerbate/increase pain intensity during wound care, [3,5,11,13,17,18,58,61,62] and excessive acute pain can lead to chronic pain. [69] Fortunately, adjunctive psychological treatments can help reduce pain [59], with few or no additional side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the major competing theories attempting to explain the analgesic potential of virtual reality postulates that virtual reality is able to effectively distract an individual from noxious stimuli (Hoffman et al, 2000;Hoffman et al, 2001;Schneider et al, 2004;Gershon et al, 2004;Hoffman et al, 2011). Furthermore, it has been hypothesized that the more attention demanding the virtual immersion is, the better it is for reducing pain (Lier et al, 2020). The purpose of this study aims to further deconstruct the basis of body illusions by further examining how perspective contributes to the affective and physiological experience of acute pain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore in this condition, there was incongruent, conflicting, visuomotor information between the visual information of their virtual embodiment and their bodily movements which they were asked to attend to (Figure 1B). One of the main differences with the extant literature on the effect of interaction in virtual environments (VE) is that we did not provide any visual cues in our VEs that could provide expectancy effects that could interfere or interact with the perspective, as previous literature has shown that environmental interaction compared to no interaction is significantly more analgesic (Lier et al, 2020). In line with the theory of attentional demand (Hoffman et al, 2019), we hypothesized that the incongruent visuomotor information experienced during the third person perspective would demand an increase in attentional capacity and therefore further distract the individuals from the painful stimuli, resulting in a relatively lower physiological stress response and lower subjective ratings compared to the first person perspective.…”
Section: Introductionmentioning
confidence: 99%